2018
DOI: 10.3389/fevo.2018.00195
|View full text |Cite
|
Sign up to set email alerts
|

A Common Yardstick to Measure the Effects of Different Extreme Climatic Events on Soil Arthropod Community Composition Using Time-Series Data

Abstract: Extreme climatic events can have profound effects on ecosystems. Climate change is causing an increase in the frequency and intensity of extreme events, which raises the probability that natural ecosystems will be exposed to subsequent or simultaneous extreme events. Exposure to multiple extreme events may involve very different abiotic stressors, which makes it hard to compare their consequences for more than a single or a few species, limiting our knowledge of community level effects. Here, we propose a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Under experimental conditions, increased densities of Arctic wolf spiders led to a decline in Collembola abundances with an accompanying decline in decomposition rates ( Koltz et al., 2018b ). Under warming conditions, collembolan abundance still declined even with low predator abundance ( Franken et al., 2018 ; Koltz et al., 2018b ). Long-term observational data from Greenland showed that Collembola declined from 1996 until 2011, during which time spider abundances increased ( Koltz et al., 2018a ).…”
Section: Biotic Interactions and Resistance To Climate Changementioning
confidence: 99%
“…Under experimental conditions, increased densities of Arctic wolf spiders led to a decline in Collembola abundances with an accompanying decline in decomposition rates ( Koltz et al., 2018b ). Under warming conditions, collembolan abundance still declined even with low predator abundance ( Franken et al., 2018 ; Koltz et al., 2018b ). Long-term observational data from Greenland showed that Collembola declined from 1996 until 2011, during which time spider abundances increased ( Koltz et al., 2018a ).…”
Section: Biotic Interactions and Resistance To Climate Changementioning
confidence: 99%